Untangling a case of dapsone-induced acute liver injury - V Meghana; Divya Ravindran; Umapathy Pasupathy (Journal of Family Medicine and Primary Care)
Dapsone hypersensitivity syndrome, although rare, may manifest with fever, rash, and multi-organ failure, mimicking other common diseases. This case study involves a 9-year-old female patient presenting with fever and acute liver injury, in which the intake of dapsone was not revealed until much later. We discuss how the diagnosis was made and the successful outcome following prompt treatment. A high index of suspicion and vigilant history-taking, along with a detailed past treatment history, can provide early clues in reaching a diagnosis. Early intervention with systemic corticosteroids improves the outcome of dapsone hypersensitivity syndrome and can prevent mortality.